Synthesis of Block and Star Copolymers by Photoinduced Radical Coupling Process - Temel, Gokhan; Aydogan, Binnur; Arsu, Nergis; Yagci, Yusuf (WILEY, 2009)
The general design for the synthesis of AB diblock, and A(2)B and AB(2) star copolymers based on the statistical coupling of poly(styrene) (PSt) and poly (methyl methacrylate) (PMMA) macromolecules containing photoreactive benzophenone is presented. For this purpose, mono- and bifunctional initiators for Atom Transfer Radical Polymerization (ATRP) bearing benzophenone group were synthesized and characterized. End- and mid-chain benzophenone functional PSt and PMMA with low molecular weights were obtained by ATRP using these initiators in the presence of CuBr/N,N,N',N '',N ''-pentamethyldiethylenetriamine (PMDETA) catalytic complex. Poly(styrene-block-methyl methacrylate) (PSt-b-PMMA) copolymers were prepared by photolysis of the solutions containing end functional PSt and PMMA in THF at lambda = 350 nm for 60 min in the presence of a hydrogen donor such as N-methyidiethanolamine (NMDEA). The proposed mechanism assumes hydrogen abstraction of photoexcited benzophenone moiety by NMDEA. Ketyl radicals resulting from abstraction reaction undergo radical-radical coupling to form benzpinaeol structure at the core. Formation of A2B and AB2 type star copolymers upon irradiation of solutions containing appropriate combinations of end- and mid-chain functional polymers was also demonstrated. (c) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2938-2947, 2009
Keywords: benzophenone; block copolymers; coupling; photopolymerization; star polymers; METHYL-METHACRYLATE; POLYMERIZATION; POLYMERS; COMBINATION; INITIATORS; PHOTOINITIATORS; POLYSTYRENE; CHEMISTRY; ACID; Polymer Science